A Neutral Glucan Extracted from Dried Ginger (Zingiberis Rhizoma): Preparation, Structure Characterization, and Immunomodulatory Activity - Sun, Long; Ni, Xing; Liu, Yulin; Jiang, Yantao; Wang, Pei-Pei; Gao, Jingdong (Planta Medica, 2025)
A neutral glucan, GJ0D, was obtained from dried ginger (Zingiberis rhizoma) by enzymatic extraction and purification with column chromatography. The fine structure of GJ0D was assessed through monosaccharide composition analysis, methylation, and two-dimensional nuclear magnetic resonance. GJ0D has a relative molecular weight of 4.0 KDa and possesses a backbone consisting of 1,4-linked α-Glcp with substitution at C-6 of Glcp by T-Glcp. Immunoactivity assessment showed that GJ0D significantly upregulates the expression of IL-6, IL-1β, and TNF-α in RAW264.7 cells. The reactive oxygen species (ROS) production was also increased in RAW264.7 cells. In addition, the expression of several proteins associated with immune activation signaling pathways including TLR4, the phosphorylation of IKKβ, and NF-κB (p100 and p52) were significantly upregulated by GJ0D. These results suggest that GJ0D could promote inflammation through the TLR4/IKKβ/P100 signaling pathway, suggesting a potential application as an immunomodulating agent.
Keywords: ginger; Zingiber officinale; Zingiberaceae; structure characterization; immunomodulatory activity; glucan